Bennie: A Revolt Against the Heterosexual Lesbian in American Cinema (A Satirical Horror Short) - Smith, Shelby (My University, 2025)
This thesis explores the intersection of queer feminist theory, monstrosity in the horror genre, and industry experience through the creation of Bennie, a satirical horror short that critiques the misrepresentation of lesbian identity in mainstream cinema. Drawing on influences such as Barbara Hammer’s experimental lesbian aesthetics, the essay reflects on the author's development as a filmmaker at Mount Holyoke College, supported by immersive experiences at Cannes, Sundance, and on a professional film set. In addition to Hammer’s work, the film explores what it means to be a monster—particularly through a queer lens—and how monstrosity can be reclaimed as a symbol of resistance, transformation, and identity. Through the lens of Bennie, the essay challenges the "heterosexual lesbian" trope perpetuated by male-directed films and reclaims horror as a vehicle for queer expression and resistance. Blending narrative and avant-garde elements, Bennie subverts traditional slasher tropes and centers on queer protagonists who resist harmful representation and erasure. The production also served as a collaborative mentorship model, offering over 40 students experiential learning opportunities. Ultimately, the essay advocates for queer-led filmmaking as a means of visibility, solidarity, and cultural change in the face of ongoing political and representational challenges.
Bennie
Keywords: short film; horror; comedy; queer-theory; monstrosity; Barbara Hammer; film production